Bladder Dysfunction and Re-Absorbable Bulking Agent Affect Success Rate in Children Underwent Endoscopic Treatment for Vesicoureteral Reflux: A Long-Term Follow-Up Study - Raffaella Cocomazzi; Alessia Salatto; Vittoria Campanella; Valentina Pastore; Cosetta Maggipinto; Gabriella Aceto; Fabio Bartoli (MDPI AG, 2021)
This paper is designed to evaluate the results (at long-term follow-up of) children affected by dilating VUR. Our attention was focused on how VUR grade, laterality, bladder dysfunction (BD), the double renal system, and the type of bulking substance may affect VUR resolution in the long-term period. The charts of 93 children with dilating VUR who underwent endoscopic treatment (ET) and with a minimum post-operative follow-up of 7 years were reviewed (mean follow-up time was 9.6 + 1.4). The majority of patients had severe and bilateral VUR. Polydimetilsiloxane or hyaluronic acid/dextranomer (PDS or Ha/Dx) were used as bulking agents. VUR persistence following endoscopic injection was independent with respect to grade, laterality, duplex renal system, and BD. However, the rate of VUR persistence was significantly higher in children with BD. Children treated with Ha/Dx had a higher rate of VUR persistence. This research demonstrated that ET of VUR is also effective at very long term follow up (and without the development of significant complications). We also showed that patients treated with absorbable bulking agents such as Ha/Dx may experience a higher recurrence rate at the long-term follow-up). We also confirm that the only preoperative condition affecting VUR recurrence was bladder dysfunction.